2010
DOI: 10.1002/ana.21991
|View full text |Cite
|
Sign up to set email alerts
|

Crossover trial of gabapentin and memantine as treatment for acquired nystagmus

Abstract: We conducted a masked, cross-over, therapeutic trial of gabapentin (1200mg/day) versus memantine (40mg/day) for acquired nystagmus in 10 patients (28-61 years; 7 female; MS: 3, poststroke: 6, post-traumatic: 1). Nystagmus was pendular in 6 patients (oculopalatal tremor: 4, MS: 2) and jerk upbeat, hemi-seesaw, torsional, or upbeat-diagonal in each of the others. Both drugs reduced median eye speed (p<0.001), gabapentin by 32.8% and memantine by 27.8%, and improved visual acuity (p<0.05). Each patient improved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 18 publications
2
54
0
1
Order By: Relevance
“…In a second trial showing that gabapentin was more successful than vigabatrin in improving APN, only patients with MS were tested. 31 In contrast to the results of a recent study in a small group of patients, 10 Shery et al 8 found that gabapentin and memantine were both effective in treating APN secondary to MS but not to other neurologic diseases, which is in accordance with our personal clinical experience. Finally, the studies from Starck 21,32 showing improvement of APN with gabapentin and memantine only tested patients with MS.…”
Section: Resultssupporting
confidence: 78%
“…In a second trial showing that gabapentin was more successful than vigabatrin in improving APN, only patients with MS were tested. 31 In contrast to the results of a recent study in a small group of patients, 10 Shery et al 8 found that gabapentin and memantine were both effective in treating APN secondary to MS but not to other neurologic diseases, which is in accordance with our personal clinical experience. Finally, the studies from Starck 21,32 showing improvement of APN with gabapentin and memantine only tested patients with MS.…”
Section: Resultssupporting
confidence: 78%
“…Although it may produce pronounced visual symptoms during the acute period, upbeat nystagmus often resolves spontaneously or converts to downbeat nystagmus. There are few clinical trials evaluating pharmacological treatments for this form of nystagmus, although 1 recent study has shown that it may be suppressed with memantine (8). Treatments similar to those for downbeat nystagmus, such as the aminopyridines (23), are also worth considering in patients with persistent upbeat nystagmus.…”
Section: Upbeat Nystagmusmentioning
confidence: 98%
“…Because potassium channels are abundant on cerebellar Purkinje cells, the aminopyridines may increase their discharge. The Gabapentin (8,9,16,45,77) Memantine (8,9,33,47,77) 4-Aminopyridine (20,23) and 3,4-diaminopyridine (19,24,21) Baclofen (14,16,29,37) Clonazepam (12) Valproate (43) Trihexyphenidyl (17,18,58) Benztropine (17) Scopolamine ( (142) enhanced Purkinje cell activity could then restore normal levels of inhibition of vertical vestibular eye movements, leading to suppression of the nystagmus (22). However, 4-aminopyridine suppresses upbeat nystagmus in some patients (23), and it may occasionally cause downbeat nystagmus to convert to upbeat nystagmus (24).…”
Section: Downbeat Nystagmusmentioning
confidence: 98%
“…Medical therapy is worth trying and gabapentin and memantin have been proposed, with clinical improvement in some patients [37,38]. The dosage of gabapentin is usually 300 mg q.i.d., up to 600 mg q.i.d.…”
Section: Discussionmentioning
confidence: 99%